Analysis of BPJS Patient Satisfaction on the Quality of Outpatient Health Services Using the IPA ( Importance Performance Analysis) Method at the Wajo Community Health Center - Fitriani; Eky Endriana Amiruddin; Andi Yaumil Bay R. Thaifur; Yeyen Andriyanti Halifi (Universitas Muhammadiyah Palu, 2025)
Importance Performance Analysis (IPA) method is a survey method used to measure patient satisfaction ( expectations ) and patient satisfaction ( reality ). The quality of health services is closely related to patient satisfaction, which is a patient's feeling resulting from the performance of the health services they receive. In the last three years, outpatient visits at the Wajo Community Health Center outpatient unit tended to fluctuate. This study aims to analyze the level of BPJS patient satisfaction with the quality of outpatient health services using the Importance Performance Analysis (IPA) method at the Wajo Community Health Center. This type of research is a descriptive survey study using a quantitative approach. The sample in this study was 100 JKN outpatients. The sampling technique in this study used accidental sampling. The results of this study indicate that the average value of the satisfaction level is 86.75%, where the level of conformity of the reliability dimension (62.25%), the tangible dimension (58.5%), the empathy dimension (113%), the responsiveness dimension (100%), and the assurance dimension (100%) so that the reliability and tangible dimensions have not been able to satisfy patients. Based on the analysis of the Cartesian diagram of 5 variables, 2 variables were found in quadrant I, 2 variables were found in quadrant II and 1 variable was found in quadrant IV. The conclusion of this study is that the highest level of suitability is the empathy dimension (113%) and the lowest level of suitability is the reliability dimension (62.25%) and tangible (58.5%). There are still services that need to be prioritized for evaluation and improvement, so that they can improve the quality of service and patient satisfaction and give a good impression to patients